2018
DOI: 10.3389/fimmu.2018.00051
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Cell or Acellular Pertussis Primary Immunizations in Infancy Determines Adolescent Cellular Immune Profiles

Abstract: IntroductionPertussis is re-emerging worldwide, despite effective immunization programs for infants and children. Epidemiological studies show a more limited duration of protection against clinical pertussis in adolescents primed with acellular pertussis (aP) vaccines during infancy than those who have been primed with whole-cell pertussis (wP) vaccines. This study aimed to determine whether memory immune responses to aP, diphtheria, and tetanus vaccine antigens following booster vaccinations at 4 and 9 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
60
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 45 publications
9
60
0
Order By: Relevance
“…Notably, the differential Th polarization was maintained even in teenagers and adults. Since polarization is maintained for years after the original priming, even after identical boosting with aP (35,43), data support the notions that wP priming enacts a differential molecular program in the vaccine-specific T cells and that this imprinting is essentially lifelong.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…Notably, the differential Th polarization was maintained even in teenagers and adults. Since polarization is maintained for years after the original priming, even after identical boosting with aP (35,43), data support the notions that wP priming enacts a differential molecular program in the vaccine-specific T cells and that this imprinting is essentially lifelong.…”
Section: Resultssupporting
confidence: 59%
“…Pertussis responses remain polarized as a function of the original priming vaccine (which correlates with another report, ref. 35), but not toward CMV/EBV. Polarization was associated with IL-4, IL-9, and TGF-β in aP-primed and IFN-γ and IL-17 in wP-primed donors.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In developing countries such as Thailand, data on pertussis burden in children is lacking to support a maternal immunization policy regarding pertussis (Forsyth et al, 2012). A modeling study has demonstrated a long duration of pertussis immunity in Thai population (Blackwood et al, 2013), whereas as much as 18% of Thai adults with prolonged cough had documented pertussis in a serological study (Siriyakorn et al, 2016). Recommendation of pertussis vaccines for Thai pregnant women justifies more information apart from the country routine disease report, in which pertussis in infants could go underrecognized.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts, including from our own group, were undertaken to characterize and compare immunological response in DTwP and DTaP primed individuals in terms of humoral (4,(13)(14)(15) and T-cell mediated immunity (16)(17)(18)(19)(20). These studies showed that both wP and aP-primed individuals are capable of strong humoral response resulting in high levels of IgG against B. pertussis antigens.…”
Section: Introductionmentioning
confidence: 99%